ANALISIS TINGKAT KESUBURAN TANAH ENTISOL AKIBAT PEMBERIAN BAHAN ORGANIK YANG DIINKUBASI MELALUI PENDEKATAN INDEKS BIOKIMIA - muhammad Basir-cyio (Universitas Tadulako, 2006)
Research of analysis of soil fertility levels using Biochemical Index was conducted on Entisol. The soil were treated with various doses of organic matters and incubated for different periods of time in a completely randomized design. The doses of organic matter were: (i) B0 (without organic matter), (ii) B1 (10 t ha-1), (iii) B2 (20 t ha-1), (iii) B3 (30 t ha-1), and (iv) B4 (40 t ha-1). The periods of incubation were 4 and 6 weeks. It was found that increased organic levels and incubation periods could improved soil fertility with the range of the biochemical index of 4-5. The addition of organic matter increased soil pH from 6,32 to 6,68 compared to no organic matter application. The availability of phosphrous increase from 14,21 ppm to 19,88 ppm as the incubation period was increased to 6 weeks. Either in 4 or 6 week periods of incubation treatments, the C-organic contents in soils treated with organic matter were significantly higher which were 0,69 and 0,82 g kg-1, respectively, as compared with control treatment.Keywords : Biochemical index, soil fertility